Defining a role of NADPH oxidase in myogenic tone development. (31st March 2022) - Mironova, Galina Yu.; Mazumdar, Neil; Hashad, Ahmed M.; El‐Lakany, Mohammed A.; Welsh, Donald G.
Abstract: Objective: The myogenic response sets the foundation for blood flow control. Recent findings suggest a role for G protein‐coupled receptors (GPCR) and signaling pathways tied to the generation of reactive oxygen species (ROS). In this regard, this study ascertained the impact of NADPH oxidase (Nox) on myogenic tone in rat cerebral resistance arteries. Methods: The study employed real‐time qPCR (RT‐qPCR), pressure myography, and immunohistochemistry. Results: Gq blockade abolished myogenic tone in rat cerebral arteries, linking GPCR to mechanosensation. Subsequent work revealed that general (TEMPOL) and mitochondrial specific (MitoTEMPO) ROS scavengers had little impact on myogenic tone, whereas apocynin, a broad spectrum Nox inhibitor, initiated transient dilation. RT‐qPCR revealed Nox1 and Nox2 mRNA expression in smooth muscle cells. Pressure myography defined Nox1 rather than Nox2 is facilitating myogenic tone. We rationalized that Nox1‐generated ROS was initiating this response by impairing the ability of the CaV 3.2 channel to elicit negative feedback via BKCa . This hypothesis was confirmed in functional experiments. The proximity ligation assay further revealed that Nox1 and CaV 3.2 colocalize within 40 nm of one another. Conclusions: Our data highlight that vascular pressurization augments Nox1 activity and ensuing ROS production facilitates myogenic tone by limiting Ca 2+ influx via CaV 3.2.